Strategic Da'wah Approaches By Lpbi Nu In Environmental Empowerment :: A Case Study on Waste Management - YOSEPIN, PIPIN (Fakultas Dakwah dan Komunikasi UIN Sunan Kalijaga, 2023)
This article explores the strategic da'wah approaches implemented by the Disaster and Climate Change Management Agency of Nahdlatul Ulama (LPBI NU) in empowering communities through waste management. This case study highlights how LPBI NU integrates da'wah principles with environmental programs to address social and ecological issues in Indonesia. Through a holistic approach, LPBI NU not only educates the public on the importance of proper waste management but also promotes behavioral change by reinforcing religious values. The research employs a qualitative method with an ethnographic approach to explore field dynamics, including the interaction between da'wah agents and communities, as well as the impact of these empowerment programs on social change at the community level. The findings indicate that the da'wah strategies employed by LPBI NU successfully raise environmental awareness and foster active participation in waste management among the community. This article contributes to da'wah studies by offering a new perspective on how da'wah strategies can be integrated with environmental empowerment programs. It also demonstrates how religious organizations can play a vital role in promoting environmental sustainability through da'wah-based approaches.